The Effect of Cake Application Towards Students’ Pronunciation Mastery At The Eighth Grade of MTs Mifatussa’adah Cibaliung Pandeglang in Academic Year 2024/2025 - Surdi, Surdi; Gumelar, Rizdki Elang; Riandi, Riandi (Journal of English Education Studies, 2024)
This research aims to investigate the effect of cake application towards students’ pronunciation mastery at the eighth grade of MTs Miftahussa’adah Cibaliung Pandeglang. The research uses the quantitative approach and quasi experimental method with pre-test and post-test design. On technique of collecting the data, this research uses a triangulation involving pre-test, treatment and post-test. The data obtained from 2 classes are experimental and control class. The experimental class was VIII A and the control class was VIII B. Each class consists of 25 students; the total number of samples is 50 students. The findings show that the experimental class’s mean score on the pre-test is 51.33, while the control class’s mean score on the pre-test is 44.00. On the other hand, the experimental class’s mean score on the pre-test is 67.20, while the mean score on control class is 59.20. The hypothesis calculating was done by using SPSS 22. The result obtained from hypothesis test is 0.00 < 0.05, it means that there is effect of cake application towards students’ pronunciation mastery at the eighth grade of MTs Miftahussa’adah Cibaliung Pandeglang.